224 INEFFECTIVE MACROPHAGE RESPONSE IN THE PERITONEAL CAVITY OF NEONATAL MICE MAY LEAD TO CEREBRAL LISTERIOSIS. (1st January 2005) - Karimi, P.; Jeyarajah, R.; Keilar, M.; John, R.; Chen, L.; Bhagat, V.; Lu, C. Y.
Abstract : Introduction: Neonates have an increased risk of sepsis and meningitis. Despite modern antibiotics and other therapies, mortality remains high. Using a murine model of intraperitoneal listeriosis, we now characterize the defective responses in the neonatal peritoneum, liver, and spleen. We find that these deficits ultimately lead to CNS infection in 100% of the neonates. In contrast, virtually no adults developed CNS listeriosis. Methods: We injected intraperitoneal Listeria monocytogenes to adult male Balb/C mice (4-6 weeks) and neonatal mice (3-5 days) at 4.2 × 105 and 150/g body weight respectively. We sacrificed groups of animals (n = 4 to10) at 1, 6, 24, 48, and 72 hours post infection for peritoneal fluid analysis (total and differential cell count as well as bacterial counts) and spleen, liver, and brain (for viable bacterial counts). Results: Both the neonates and adult mice mount an early neutrophilic response to intraperitoneal listeria infection. However, at 48 hours post infection there was a major difference in the macrophage response wherein macrophages constituted 21% and 51% of the cellular response in neonates and adults respectively (p < .001). There was a persistent neutrophilic response in the neonate at 72 hours (72% as compared to 17% in the adult, p < .001). Lymphocytes began to appear at 48 hours in adults, with no change in neonates. Also, listeria continued to proliferate in the neonatal peritoneum, spleen, and liver, whereas infection was contained at 72 hours in the adult. None of the adults and all of the neonates had brain infection at 72 hours. Conclusion: In the adult, an effective antilisterial response is characterized by an early robust neutrophilic infiltrate that converts into a predominantly macrophage response over the course of days. Although neonates mount the neutrophilic response, they fail to convert this into a macrophage response. As a result, infection is not contained in the peritoneum, spleen, and liver and spreads to the brain. The reason for the inability of the neonate to convert the neutrophilic response into one rich in macrophages is being actively pursued in our laboratory. Our preliminary studies reveal the up regulation of MCP-1 (macrophage chemotactic factor-1) at 24 hours post infection in the peritoneal exudate of the adult mice when compared to the neonatal mice.